Lower Ordovician (Tremadocian) conodonts from Broom Point and Green Point, western Newfoundland. - BAGNOLI, GABRIELLA; BARNES C. R.; STEVENS R. K. (1987)
Lower Ordovician conodonts are reported from continental slope deposits of yhe Cow Head Group from sections at Broom Point North and Green Point, western Newfoundland. The conodont fauna is dominated by species of the genus Cordylodus Pander. The apparatus of Cordylodus consists of two morphotypes in a type IIIB apparatus. One new genus and three new species are described. New evolutionary relatioships are suggested beteewn different species of Cordylodus. An evolutionary sequence from Eoconodontus notchpeakensis through Cordylodus primitivus, C. proavus, C. caboti, C. intermedius, to C. angulatus is proposed.